The renoprotective effect of curcumin in cisplatin-induced nephrotoxicity - Ugur, Siddik; Ulu, Ramazan; Dogukan, Ayhan; Gurel, Ali; Yigit, Irem Pembegul; Gozel, Nevzat; Ilhan, Necip (Taylor & Francis Ltd, 2015)
The polyphenol curcumin has several pharmacological effects, including antioxidant, anti-inflammatory and anti-cancer features. In this study, we evaluated the effects of curcumin in cisplatin-induced nephrotoxicity in rats. Male Wistar rats were divided into four groups: (1) control; (2) cisplatin (7 mg/kg body weight, intraperitoneal as a single dose); (3) curcumin (100 mg/kg via gavage, for 10 days); and (4) cisplatin and curcumin. The cisplatin-treated rats exhibited kidney injury manifested by increased serum urea and creatinine (p < 0.05). The kidney tissue from the cisplatin treated rats also exhibited a significant increase in the malondialdehyde (MDA) levels (p < 0.05). The treatment with curcumin prevented a rise in the serum urea, creatinine and MDA levels when compared to the control group kidneys (p < 0.05). The analysis the nicotinamide phosphoribosyltransferase (NAMPT) and sirtuin (SIRT) proteins (SIRT1, SIRT3 and SIRT4), which play important roles in the resistance to stress and the modulation of the threshold of cell death, showed similar trends (p < 0.05). In the cisplatin-only treated rats, the induced renal injury decreased the levels of the NAMPT and SIRT proteins. Conversely, the curcumin increased the levels of the NAMPT and SIRT proteins in the cisplatin-treated rats (p < 0.05). These data suggest that curcumin can potentially be used to reduce chemotherapy-induced nephrotoxicity, thereby enhancing the therapeutic window of cisplatin.
Keywords: Cisplatin; curcumin; nephrotoxicity; oxidative stress; sirtuin